Increased short- and long-term risk of sleep disorders in people with traumatic brain injury. Issue 2 (7th February 2021) - Wang, Yu-Jia; Chang, Wei-Chiao; Wu, Chung-Che; Chiang, Yung-Hsiao; Chiu, Wen-Ta; Chen, Kai-Yun; Chang, Wei-Pin
ABSTRACT: This study aims to evaluate the relationship between traumatic brain injury (TBI) and sleep disorders (SDs). We first initiated a questionnaire-based clinical survey to assess sleep problems in the early stage after a TBI, followed by a population-based cohort study to evaluate the long-term risk of SDs in TBI patients. For short-term clinical survey, mild (m)TBI patients and healthy controls were recruited to evaluate the sleep quality and daytime sleepiness using the Pittsburg Sleep Quality Index (PSQI) and Epworth Sleepiness Scale (ESS) within two weeks after a TBI. For long-term observation, a 5-year nationwide population-based cohort study that utilized a large administrative database was conducted. In the short-term survey, 236 mTBI patients and 223 controls were analyzed. Total scores of the PSQI and ESS were significantly higher in mTBI patients than in the controls. In the long-term cohort study, 6932 TBI cases and 34, 660 matched controls were included. TBI cases had a 1.36-fold greater risk of SDs compared to the non-TBI controls during the 5-year follow-up period. Results showed that patients with TBI had a significantly higher risk of SDs than did controls both in the early stage and during a 5-year follow-up period.